If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 12 = 55x + -70 Reorder the terms: 12 + 15x = 55x + -70 Reorder the terms: 12 + 15x = -70 + 55x Solving 12 + 15x = -70 + 55x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-55x' to each side of the equation. 12 + 15x + -55x = -70 + 55x + -55x Combine like terms: 15x + -55x = -40x 12 + -40x = -70 + 55x + -55x Combine like terms: 55x + -55x = 0 12 + -40x = -70 + 0 12 + -40x = -70 Add '-12' to each side of the equation. 12 + -12 + -40x = -70 + -12 Combine like terms: 12 + -12 = 0 0 + -40x = -70 + -12 -40x = -70 + -12 Combine like terms: -70 + -12 = -82 -40x = -82 Divide each side by '-40'. x = 2.05 Simplifying x = 2.05
| 4-3x=22 | | 6x-(3x+5)= | | 8x^2+9x+3=0 | | y=8x^2+26x | | 9n-29=43 | | 5n+6p+7n+p= | | (n+3)*9=45 | | (n-8)*6=30 | | x^2+12x-25=0 | | -2+-2=-2(x-5)-6 | | 77-3x=24x+14 | | 5x+35=14x-36 | | 1+2[3(x-1)-5(2x-3)]=2x-7 | | 4x+5-10x=8+3x+12 | | 5x+31=tx+11 | | 4x^2+7x-8=0 | | 8b-4(b-2)=42 | | -6-20=-2n | | 2x+10=110-10x | | 8x+9=2x-13 | | 4x=8x+6 | | x+4+5+2=3+2+2x | | 2*(x+3)-3(x+1)=x-13 | | b(b+2)+4b^2=5b^2+9b+8 | | 10x-13=3x-7 | | y=2x^3-7x^2-15x | | x+11=8+x | | x+11=8+c | | n-9=7 | | n+27=44 | | a-4=3a-6 | | 5y-10=2y-3x+11 |